Automated Scheduling System for FCSIT / Ooi Ling Sern - Ooi, Ling Sern (2002)
The final year thesis project as entitle, "Automated Scheduling System for FCSIT", is required o build a scheduling system for Faculty of Computer Science and Information Technology (FCSIT). The objective of this project is to improve the current scheduling process from a manual system to a computerized system. At the end of the project, an automated scheduling system should be produce. This system also should be generic for most timetabling in school or any higher learning institutions.